Identifying The Distribution Of Golden Snail (Pomacea Canaliculata) During The Rice Crop Harvest (Oryza Sativa L) In Sumberaji Village, Kabuh District, Jombang Regency - Widi Ardiansyah; Zulfikar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aimed to examine the distribution of the golden apple snail (Pomacea canaliculata) and its ecological associations during the rice harvest stage (Oryza sativa L.) in Sumberaji Village, Kabuh District, Jombang Regency. Fieldwork was conducted from May to June 2025 using a descriptive quantitative design. Data were collected through purposive sampling across four observation plots, each measuring one square meter. Statistical analysis included Pearson correlation to assess the relationship between environmental variables and snail abundance, while the distribution patterns of temperature and pH were evaluated using the Chi-Square Goodness of Fit test. A total of fourteen individuals were recorded across all plots, resulting in an average density of 0.875 individuals per square meter. The highest abundance was observed in the second plot, where water temperature and pH were within the optimal ecological range. The lowest abundance occurred in the fourth plot, with only one individual recorded. Correlation analysis revealed no significant relationship between environmental factors and snail abundance (r = –0.28 for temperature; r = –0.31 for pH; p > 0.05). The Chi-Square test results indicated that the distribution of temperature (χ² = 0.097; p > 0.05) and pH (χ² = 0.065; p > 0.05) did not differ significantly from an even distribution pattern. These findings indicate that temperature and pH conditions at the study site were relatively homogeneous across plots and did not represent dominant determinants of golden apple snail distribution. Other ecological variables, including food availability, vegetation structure, and biotic interactions, are likely to exert a stronger influence on population variability.